2009
DOI: 10.1126/scisignal.2000610
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of MicroRNA-126 by Apoptotic Bodies Induces CXCL12-Dependent Vascular Protection

Abstract: Apoptosis is a pivotal process in embryogenesis and postnatal cell homeostasis and involves the shedding of membranous microvesicles termed apoptotic bodies. In response to tissue damage, the CXC chemokine CXCL12 and its receptor CXCR4 counteract apoptosis and recruit progenitor cells. Here, we show that endothelial cell-derived apoptotic bodies are generated during atherosclerosis and convey paracrine alarm signals to recipient vascular cells that trigger the production of CXCL12. CXCL12 production was mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
1,083
3
17

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,195 publications
(1,131 citation statements)
references
References 41 publications
12
1,083
3
17
Order By: Relevance
“…32,33 Electron microscopy of the cell-free fraction from G-CSF-mobilized bone marrows revealed large numbers of vesicles resembling exosomes ( Figure 4A) and others (not shown) morphologically similar to neutrophilderived apoptotic bodies described in the bone marrow. 34 Similar, but fewer, particles were visualized in the cell-free fraction of non-mobilized bone marrows (not shown).…”
Section: Microvesicle Production and Transfer To Hematopoietic Stem/pmentioning
confidence: 83%
“…32,33 Electron microscopy of the cell-free fraction from G-CSF-mobilized bone marrows revealed large numbers of vesicles resembling exosomes ( Figure 4A) and others (not shown) morphologically similar to neutrophilderived apoptotic bodies described in the bone marrow. 34 Similar, but fewer, particles were visualized in the cell-free fraction of non-mobilized bone marrows (not shown).…”
Section: Microvesicle Production and Transfer To Hematopoietic Stem/pmentioning
confidence: 83%
“…28,29 Previous studies have suggested that circulating miRNAs may act as extracellular communicators because they could be transferred to VECs and regulate atherosclerotic processes. [30][31][32] Extracellular miRNAs are especially adept at mediating gene regulation among cells in a microenvironment. 33 In this regard, subintimal inflammation and atherosclerotic lesions, which harbor complex multicellular microenvironments, may be a nexus of miRNA-based signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, miR‐126 attenuates the expression of CXCR4 on c‐Kit + cells situated in the bone marrow while increasing the expression of SDF‐1α in ischaemic tissues, triggering mobilization of c‐Kit + cells from the bone marrow and favouring their homing into the injured site 59, 68.…”
Section: Molecular Signatures Associated With Pc Homingmentioning
confidence: 99%